A Critical Review of Medemer from Ideological Perspectives - Tefera Assefa (African Journal of Political Science)
Medemer, both as a book and as an idea, is trapped between two extremes: admiration and rejection. Writers from both ends offer their thoughts, criticisms, and reviews of Medemer. The aim of this article is to analyze Medemer from an ideological perspective. Raising some political and policy questions about Medemer’s application is also the aim of this article. This article used a qualitative research approach and comparative and critical research methods. Secondary sources of data were used to compare Medemer with various political ideologies. Ideologically, Medemer meets the three criteria (critics of the present order, vision of the future society, and theory of change). Medemer is a “blended ideology” that combines concepts, principles, and ideas from liberalism, socialism, conservatism, and fascism. Furthermore, Medemer ideology attempted to combine concepts from opposing political ideologies and proposed it as a solution to Ethiopia’s complex sociopolitical and economic problems. Despite the government’s claim that Medemer is Ethiopia’s redeemer, several political questions remain unanswered given the country’s current situation. Therefore, the country’s complicated sociopolitical and economic problems under the regime of the Prosperity Party challenged the applicability of Medemer. Is Medemer thus the sole (or perhaps the only) instrument, policy framework, ideology, and mechanism for resolving Ethiopia’s multiple, dynamic, and complex socio-political problems? These remain a point of contention among academics and politicians.